Annual reports in medicinal chemistry. - Doherty, Annette M. (Annette Marian), 1961-; Greenlee, William F. (Academic Press, 2000)
Annual Reports in Medicinal Chemistry provides timely and critical reviews of important topics in medicinal chemistry together with an emphasis on emerging topics in the biological sciences which are expected to provide the basis for entirely new future therapies.